Hubungan Teknik Umpan Balik Dengan Motivasi Belajar Siswa - Hayatul Mardhiyah; Hanifa Zahara; Ikhsan Maulana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The relationship between feedback techniques and student learning motivation is an important topic in the educational context. Properly provided feedback can influence students' motivation to learn and improve their academic performance. In this journal, we explore the different types of feedback techniques that can be used in education and how they can influence students' learning motivation. This study involved students from various levels of education and used observation, interviews and survey methods to collect data. The research results show that feedback techniques that are constructive and specific tend to increase students' learning motivation, while feedback that is critical or feedback that is unclear can reduce students' learning motivation.